2003
DOI: 10.1124/jpet.102.047142
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prostaglandin I2in the Gene Expression Induced by Mechanical Stress in Spinal Ligament Cells Derived from Patients with Ossification of the Posterior Longitudinal Ligament

Abstract: Ossification of the posterior longitudinal ligament of the spine (OPLL) is characterized by ectopic bone formation in the spinal ligaments, and mechanical stress has been suggested to play an important role in the progression of OPLL. To identify the genes that participate in OPLL, the differential display reverse transcription-polymerase chain reaction (RT-PCR) method was used. A 283-base pair cDNA fragment corresponding to prostaglandin I 2 (PGI 2 ) synthase was highly expressed in OPLL cells compared with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 24 publications
1
19
0
1
Order By: Relevance
“…Attempts have been made to simulate the mechanical stress in vitro, mostly with a motor-driven uniaxial sinusoidal cyclic stretch [18]. The system induced the transcription of messenger ribonucleic acids of several growth factors, including BMP-2, BMP-4, prostaglandin I 2 synthase, and osteoblast-specific transcription factor in the cells from OPLL patients [9,19,24,30]. At the same time, several studies have suggested that ER stress response can be activated by mechanical stress in some cellular pathological processes, such as apoptosis in rat annulus fibrosus cells or human connective tissue cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to simulate the mechanical stress in vitro, mostly with a motor-driven uniaxial sinusoidal cyclic stretch [18]. The system induced the transcription of messenger ribonucleic acids of several growth factors, including BMP-2, BMP-4, prostaglandin I 2 synthase, and osteoblast-specific transcription factor in the cells from OPLL patients [9,19,24,30]. At the same time, several studies have suggested that ER stress response can be activated by mechanical stress in some cellular pathological processes, such as apoptosis in rat annulus fibrosus cells or human connective tissue cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…22 Prostacyclin synthase levels in ligament cells from OPLL patients have been shown to be elevated after applying mechanical stress and induced osteogenic differentiation via the PGI 2 / cyclic adenosine monophosphate pathway. 97 Mechanical stress also induces mRNA expression of alkaline phosphatase, osteopontin, BMP-2, BMP-4, BMP receptors, 121 and mRNA expression of Cbfa1, Type I collagen, osteocalcin, integrin b1, 43 and endothelin-1. 47 The P2Y1 purinoceptor subtypes, intensively expressed in OPLL cells, responded to mechanical stress-induced extracellular adenosine triphosphate, which stimulated OPLL progression.…”
mentioning
confidence: 99%
“…Addition of BMP-2 or conditioned medium from OPLL cells exposed to cyclic stretching enhanced the expression of ALP in OPLL cells, and this effect was significantly blocked by an anti-BMP antibody (20). As suggested by the cyclic stretch-induced PGI 2 synthase expression (Table 1), enhanced release of prostacyclin was observed in OPLL cells (8). Furthermore, addition of beraprost, a stable Fig.…”
Section: Responses Of Opll Cells To Mechanical Stressmentioning
confidence: 78%